A Preliminary Assessment of Shade and Shelter Use in Paddock-Kept Horses in Australia: A Pilot Study - Marina Douglas; Hayley Randle (International Journal of Equine Science)
There is increasing evidence to support the recommendation of providing horses with adequate shade, either natural or man-made, to safeguard their welfare. Weather conditions, particularly extreme temperatures, influence horses' shade-seeking behavior and ability to thermoregulate. However, there is limited research on other factors that may influence equine shade-seeking behavior. The aim of this study was to investigate the influence of weather conditions and shade type available on horses’ shade-seeking behavior in non-extreme conditions, i.e. not in the intensity of summer, using animal-based behavioral indicators. Shade-seeking behavior of 19 university-owned horses was observed over a period of six days. Horses were kept in groups (n = 7 to 12 individuals) in paddocks with free access to an artificial shelter (AS) and natural shade (NS). The location of each horse was recorded at hourly intervals during the day along with the time of day, ambient temperature, and prevailing weather conditions. Shade use was not related to the time of day, and horses spent most of their time in non-shade (85.5%), compared to natural shade (10.2%) and artificial shade (4.3%; H2 = 187.85, p < 0.0001). However, horses were more likely to seek artificial shade in foggy or cloudy conditions and natural shade when it was partly cloudy (Chi212 = 30.14; p < 0.05). Horses preferred natural to artificial shade, spending 78% of their shade-time in natural shade. Although horses spent the majority of their time not in the shade in this study, it does not mean that shade is not important for the thermal comfort and wellbeing of the horse. Horses still displayed shade-seeking behavior during conditions not deemed extreme, for example, in fog and reduced visibility conditions. Further research could be beneficial to understanding shade-seeking behavior in horses in order to determine what constitutes acceptable shade provision to optimize horse welfare.